The conflict in Sri Lanka and its implications for South Asian and regional security - Hellman-Rajanayagam, Dagmar (Universiti Kebangsaan Malaysia, 1999)
The note describes a research project on the security implications of the conflict in Sri Lanka for South Asia and the wider region conducted in Germany, the United Kingdom, France, India and Sri Lanka from December 1996 to December 1997. It looked at the question whether the fall-out of the conflict in Sri Lanka - the presence of refugees in India and western countries, and the activities of Tamil militant groups abroad — constitutes a security risk for the countries concerned. It was found that all the western countries concerned, and India, consider the security risks attendant on the presence of both Tamil refugees and of Tamil militant organisations as minor to negligible. While some disturbance of public law and order and demands on welfare expenditure can be considered as risks, these remain within the scope of the law enforcing agencies. India has taken steps to deal with the threat to national security emanating especially from Tamil groups taking refuge in India, and while for a time this threat was quite severe, it now considers it to have been brought under control. This throws doubts on the wisdom of the US to declare the Liberation Tigers of Tamil Eelam (LTTE) a terrorist organisation in 1997.